2016
DOI: 10.1002/polb.24113
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical hybrid transiency: A fully transient li-ion battery based on insoluble active materials

Abstract: Transient Li‐ion batteries based on polymeric constituents are presented, exhibiting a twofold increase in the potential and approximately three orders of magnitude faster transiency rate compared to other transient systems reported in the literature. The battery takes advantage of a close variation of the active materials used in conventional Li‐ion batteries and can achieve and maintain a potential of >2.5 V. All materials are deposited form polymer‐based emulsions and the transiency is achieved through a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…Among them, cyclic poly(phthalaldehyde) (PPHA) with a low ceiling temperature (T c = −43 °C) has received broad interest due to its promising mechanical properties, ease of synthesis, and fast depolymerization rates. To our best knowledge, most of existing reports on transient power sources are about energy storage devices, [16][17][18] and only transient energy harvesters whose degradation requires aqueous solution have been demonstrated. [13] Tang et al reported a programmable payload release system from PPHA-based microcapsules, whose release rates could be controlled by the composition and concentration of the salt/acidic methanol solution.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Among them, cyclic poly(phthalaldehyde) (PPHA) with a low ceiling temperature (T c = −43 °C) has received broad interest due to its promising mechanical properties, ease of synthesis, and fast depolymerization rates. To our best knowledge, most of existing reports on transient power sources are about energy storage devices, [16][17][18] and only transient energy harvesters whose degradation requires aqueous solution have been demonstrated. [13] Tang et al reported a programmable payload release system from PPHA-based microcapsules, whose release rates could be controlled by the composition and concentration of the salt/acidic methanol solution.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[15] Briefly, to fabricate substrates, PVA (Mw: 61 000 g mol À1 , 98.0-98.8% hydrolyzed, Sigma Aldrich) was used as received. [15] Briefly, to fabricate substrates, PVA (Mw: 61 000 g mol À1 , 98.0-98.8% hydrolyzed, Sigma Aldrich) was used as received.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…The variation of the PVA substrate properties as a function of swelling strain [15] and true stressstrain curve of the electrode layer were applied for the analysis. Two dimensional symmetry (about x-and y-axes) of the structures allows for simplification of the model to quarter symmetric.…”
Section: Fem Simulationmentioning
confidence: 99%
See 2 more Smart Citations